TRENDS IN DRUG DEPENDENCE - Rehman, Aziz -ur-; Saeed, A.K.; Zaman, Safdar (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: Data of drug dependence from 9 Drug Abuse Treatment Centres in Pakistan is presented. This comprises a 6 years' period, that is from 1980 upto 1985. A total number of 21,972 drug dependents were admitted in these centres for treatment. Out of this number 20,840 (94.8%) cases were in the age group of 15-35 years. The trend of heroin abuse has substantially increased over the past decade as compared to conventional and traditional drugs. In this data 18,676 cases i.e. 85% were heroin dependent. The results of treatment showed that 50% cases were addiction free, 34% relapsed and 16% could not be traced in six months. Area identification showed that 82% of these cases belonged to urban and 28% to rural areas. 74% were employed and 28% unemployed. Majority of these cases i.e. 80% started drug abuse under the influence of peer group and friends (bad company).